2020
DOI: 10.1371/journal.pone.0227592
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide enrichment screen identifies NUMA1-loss as a resistance mechanism against mitotic cell-death induced by BMI1 inhibition

Abstract: BMI1 is a core protein of the polycomb repressive complex 1 (PRC1) that is overexpressed in several cancer types, making it a promising target for cancer therapies. However, the underlying mechanisms and interactions associated with BMI1-induced tumorigenesis are often context-dependent and complex. Here, we performed a drug resistance screen on mutagenized human haploid HAP1 cells treated with BMI1 inhibitor PTC-318 to find new genetic and mechanistic features associated with BMI1-dependent cancer cell prolif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…( Chu et al, 2016 ; Torii et al, 2020 ). The absence of NUMA1 resists cell death in the PTC-318 cell ( Gisler et al, 2020 ), and the alternative splicing of the gene is associated with the cellular proliferation and centrosome amplification in the epithelial cells ( Sebestyén et al, 2016 ). SAFB1 regulates RNA processing and neuronal function rendering the chromatin permissive for DNA damage signaling and myogenic differentiation ( Hernandez-Hernandez et al, 2013 ; Rivers et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…( Chu et al, 2016 ; Torii et al, 2020 ). The absence of NUMA1 resists cell death in the PTC-318 cell ( Gisler et al, 2020 ), and the alternative splicing of the gene is associated with the cellular proliferation and centrosome amplification in the epithelial cells ( Sebestyén et al, 2016 ). SAFB1 regulates RNA processing and neuronal function rendering the chromatin permissive for DNA damage signaling and myogenic differentiation ( Hernandez-Hernandez et al, 2013 ; Rivers et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…To study the role of kinase deregulation in tumor initiation and/or progression, Robinson-Garcia et al developed a CRISPR-Cas9 systematic approach to identify synthetic lethal interactions for kinase deficiencies to different DNA-damaging chemotherapeutic agents using HAP1 (Robinson-Garcia et al, 2019). Another technique to exploit synthetic lethality in HAP1 was conducted by Gisler et al, by performing a genome-wide screen for gene disruptors that could result in resistance to pharmacological inhibition of BMI1 on HAP1 by exposing mutagenized HAP1 to low concentrations of the BMI1-inhibitor PTC-318 (Gisler et al, 2020).…”
Section: Oncologymentioning
confidence: 99%
“…Several studies have documented that BMI-1 overexpression is inversely correlated to the expression of tumor suppressor genes such as PTEN and p16 [ 30 ]. Gisler et al [ 31 ] have shown that upregulation of BMI-1 significantly induces cancer cells proliferation. Furthermore, it has been shown that elevated BMI-1 mRNA level contributes to anti-cancer drugs resistance.…”
Section: Main Textmentioning
confidence: 99%